2010
DOI: 10.1111/j.1745-3933.2009.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

A new dynamo pattern revealed by solar helical magnetic fields

Abstract: A previously unobservable mirror asymmetry of the solar magnetic field – a key ingredient of the dynamo mechanism which is believed to drive the 11‐year activity cycle – has recently been measured. This was achieved through systematic monitoring of solar active regions carried out for more than 20 years at observatories in Mees, Huairou and Mitaka. In this Letter we report on detailed analysis of vector magnetic field data, obtained at Huairou Solar Observing Station in China. Electric current helicity (the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
101
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 32 publications
14
101
1
3
Order By: Relevance
“…They found that the latter is generally stronger, except during the early years of a solar cycle. Further evidence for the dependence of the chirality of features in the solar atmosphere on the phase of the solar cycle comes from SXR loops (Zhang et al 2010b) and active-region magnetic fields (Zhang et al 2010a).…”
Section: Hemispheric Trendsmentioning
confidence: 99%
“…They found that the latter is generally stronger, except during the early years of a solar cycle. Further evidence for the dependence of the chirality of features in the solar atmosphere on the phase of the solar cycle comes from SXR loops (Zhang et al 2010b) and active-region magnetic fields (Zhang et al 2010a).…”
Section: Hemispheric Trendsmentioning
confidence: 99%
“…During the minimum phase of the solar activity cycle only these signs sometimes occur. Zhang et al (2010) give the approximative value 10 −5 G 2 /cm for the observed smallscale current helicity. With the radial scale of 100 Mm and with B rBφ 10 4 G 2 , one only needs a magnetic Reynolds number Rm of the fluctuations of order 10 to fulfill the numerical constraints.…”
Section: Discussionmentioning
confidence: 99%
“…at the solar surface, all showing that it is negative (positive) in the northern (southern) hemisphere (Hale 1927;Seehafer 1990;Rust & Kumar 1994;Abramenko et al 1996: Bao & Zhang 1998Pevtsov 2001;Kleeorin et al 2003;Zhang et al 2010Zhang et al , 2012. Here the notation b denotes the fluctuating parts of the total magnetic field in the form B =B + b.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 2010) knowledge of its radial and colatitudinal distributions, here expressed through the functions f 1 (r) and f 2 (θ), is quite preliminary. Therefore, we adopt only simple parametrizations and explore a number of options to investigate the sensitivity of butterfly diagrams to the underlying assumptions.…”
Section: Mean-field Dynamosmentioning
confidence: 99%